2020
DOI: 10.1155/2020/5621461
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Epilepsy in Lubumbashi, Democratic Republic of Congo

Abstract: Background. Epilepsy is one of the most common neurological conditions, but the majority of epilepsy patients in sub-Saharan countries do not receive appropriate treatment. In the Democratic Republic of Congo (DRC), particularly in Lubumbashi, very few epidemiological studies on epilepsy have emerged. This study aims to analyze demographic characteristics, semiology of epileptic seizures, and their etiologies in patients followed in hospital. Methods. This is a prospective descriptive study that enrolled 177 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…We observed the absence of genetic studies on epilepsy from African populations, despite the high prevalence of this disorder in Africa. Fodjo et al ( 168 ) reported the prevalence of epilepsy in West Africa as 13.14 per 1,000 persons, Akinsulore and Adewuya ( 169 ) reported an incidence rate of 5.3–37 per 100 persons in Nigeria, Esterhuizen et al ( 167 ) reported a median occurrence of 14.2 per 1,000 in Sub-Saharan Africa while Mukuku et al ( 170 ) reported 5.2–74 per 100 persons with epilepsy. Although variances occur depending on the studied region, there is remarkably higher prevalence of epilepsy in low- and middle-income countries (LMICs) than in developed nations ( 171 ).…”
Section: Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We observed the absence of genetic studies on epilepsy from African populations, despite the high prevalence of this disorder in Africa. Fodjo et al ( 168 ) reported the prevalence of epilepsy in West Africa as 13.14 per 1,000 persons, Akinsulore and Adewuya ( 169 ) reported an incidence rate of 5.3–37 per 100 persons in Nigeria, Esterhuizen et al ( 167 ) reported a median occurrence of 14.2 per 1,000 in Sub-Saharan Africa while Mukuku et al ( 170 ) reported 5.2–74 per 100 persons with epilepsy. Although variances occur depending on the studied region, there is remarkably higher prevalence of epilepsy in low- and middle-income countries (LMICs) than in developed nations ( 171 ).…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Although variances occur depending on the studied region, there is remarkably higher prevalence of epilepsy in low- and middle-income countries (LMICs) than in developed nations ( 171 ). Over three-fourths of persons having epilepsy live in the LMICs, and about two-thirds of these cases have unknown etiology ( 167 , 170 ). Although some reports suggest a relationship between epilepsy and CNS infections in Africa ( 168 , 172 ), the etiology of most epilepsy remains unknown.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…In a study conducted in the southern Indian city of Kerala, 39% of citizens surveyed called epilepsy a hindrance to marriage, and 55% of patients hid their diagnosis from their spouse. This was also the case in the populous province of the Republic of the Congo, in Lubumbashi, where epilepsy also posed a threat to women due to the likelihood of losing the chance to marry [20][21][22]. Severe seizures with a change in consciousness, accompanied by inappropriate behavior of patients, caused bewilderment on the part of others, which negatively affected the psych emotional status of patients.…”
Section: Resultsmentioning
confidence: 89%
“…3 In a study conducted in Lubumbashi, they enrolled 177 patients with epilepsy, the etiology was found in 38.4% (68/177), and 26.5% (18/68) of them had NCC. 13 The diagnosis of NCC depends on brain imaging, which is expensive (about US$300) in Lubumbashi where there is no magnetic resonance imaging device (only CT scan) and patients do not have access to this examination, which is only available in two hospitals. As for the serology, it is not available throughout the city of Lubumbashi; we were however able to collect serum samples and obtain serological confirmation by sending these for an enzyme-linked immunoelectrotransfer blot assay to another country (Zambia), and the results came after patients had been managed as described.…”
Section: Discussionmentioning
confidence: 99%